Політичний чинник впливу на трансформацію орнаментації традиційної кераміки Лівобережної України - Щербань, Анатолій Леонідович (My University, 2015)
Охарактеризовано вплив політичних факторів на трансформації традиційної орнаментики кераміки Дніпровського Лівобережжя (до початку останнього десятиліття ХІХ ст.).

The ornamentation of the traditional ceramics of the Left bank Ukraine is a polyhedral scene, which been progressing under influence of row of conditions. In particular, immediate played role changes in politic status of researched territory, her place in politic of neighboring countries. Before that nobody haven’t analyzed in scientific columns, concerning transformations of decor of the ceramic products.
Keywords: орнамент, ornaments; гончарство, pottery